International Law Principles Recognized by Civilized Countries (A Perspective) - Arief Fahmi Lubis (International Forum of Researchers and Lecturers, 2023)
Human rights protect individuals, groups, or property. The nation or state officials as part of the country have an international obligation to protect the community and their property, where international human rights standards are established and developed in various international forums. This study aims to provide a critical review of the Convention related to Human Rights which guarantees the right of everyone to be treated equally before the law regardless of race, color, origin, and ethnicity, which also forms the Committee on the Elimination of Racial Discrimination to supervise its implementation. This qualitative research used a descriptive approach to collect data systematically, factually, and quickly in accordance with the description when conducting research. The results of this study showed that the principles of human rights guide law enforcement in prosecuting criminals. These principles emphasize the importance of supervision (including clarity in the chain of command) of law enforcement agencies. These principles also explain in detail the guarantee of the right to life fulfillment.